Description of the Condition of the Betawi Language in Future Developments - Iskandarsyah Siregar (BIRCU, 2023)
This study analyzes Betawi language users in the Jakarta area. The purpose of this research is to find out the health vitality of the Betawi language in the future, the factors that can cause the Betawi language to be endangered, and how the solution is to maintain the existence of the Betawi language. The theory used in this research is sociolinguistic, and the supporting theory is cultural sociology. The method used in this study is the cauldron quantity method or mixed methods. This research step combines two forms of research that have existed before: qualitative and quantitative. This method is used to obtain more complete, valid, reliable and objective and describes the results of data collection by researchers through observation of the statements of research subjects. This study used observation techniques and questionnaires (questionnaires). Observation is a data collection technique carried out through observation, which involves recording the condition or behaviour of the subject. The questionnaire technique (questionnaire) is a list of questions about the problem or area being investigated. The results obtained are calculations of the current use of the Betawi language in order to determine the health vitality of the Betawi language in the future. Observation is a data collection technique carried out through observation, which involves recording the condition or behaviour of the subject. The questionnaire technique (questionnaire) is a list of questions about the problem or area being investigated. The results obtained are calculations of the current use of the Betawi language in order to determine the health vitality of the Betawi language in the future. Observation is a data collection technique carried out through observation, which involves recording the condition or behaviour of the subject. The questionnaire technique (questionnaire) is a list of questions about the problem or area being investigated. The results obtained are calculations of the current use of the Betawi language in order to determine the health vitality of the Betawi language in the future.